Campaign-Based Citizen Science for Environmental Mycology: The Science Solstice and Summer Soil-Stice Projects to Assess Drug Resistance in Air- and Soil-Borne Aspergillus fumigatus. (18th September 2020) - Shelton, Jennifer M. G.; Fisher, Matthew C.; Singer, Andrew C.
Citizen science projects are often undertaken for ecological and environmental research purposes but also have great potential for use in microbiology research to track the emergence and spread of pathogens in the environment. Science Solstice and Summer Soil-stice are mycology citizen science projects aimed at collecting air and soil samples, respectively, in the United Kingdom (UK), that will be used to culture Aspergillus fumigatus fungal spores and to determine their drug resistance. A. fumigatus plays an important role in the environment as a decomposer of plant material, but is also a human lung pathogen. Infection with drug-resistant spores can lead to a worse clinical outcome for the patient. On the four solstice and equinox days between June 2018 and March 2019, volunteers were asked to collect air samples from their homes and workplaces and return them to our lab in Freepost envelopes (UK only) or were reimbursed for postage if returning samples from outside of the UK. An additional round of samples was requested from UK volunteers' gardens and/or compost on the June 2019 solstice. In total, 787 volunteers returned 2, 132 air samples and 509 soil samples, which grew a total of 7, 991 A. fumigatus colonies. The estimated total cost of the study was £2, 650, the equivalent of £0.33 per A. fumigatus colony grown. Incorporating citizen science into the environmental surveillance of drug-resistant A. fumigatus allowed for the simultaneous collection of hundreds of environmental samples across the entire UK on the same day. The insights generated from this study would not be practical in the absence of public participation, which offers opportunities to ask scientific questions that were previously un-askable.